Xylanase Superproducer: Genome Sequence of a Compost-Loving Thermophilic Fungus, Thermomyces lanuginosus Strain SSBP - Mchunu, Nokuthula Peace (American Society for Microbiology, 2013)
We report here the draft genome sequence of Thermomyces lanuginosus strain SSBP, which was isolated from soil in South Africa. This fungus produces the largest amount of xylanase ever reported in the literature.